2009
DOI: 10.1038/ajg.2009.73
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of an Evidence-Based Lecture and Clinical Prompt as Methods to Improve Quality of Care in Colorectal Cancer Screening

Abstract: Clinical prompts are superior to evidence-based lectures for improving physician colorectal cancer screening practices. These prompts are simple low-cost measures that can improve quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…14 In another cohort trial, clinical prompts on the patient medical record significantly improved the probability that a screening test would be ordered. 15 Even when patients have had a prior colonoscopy, a physician reminder increases the use of surveillance colonoscopy. 16 Knowing that the recommendation of CRC screening is one of the strongest predictors of screening, it is important to discern the differences between those persons who receive a recommendation for CRC colonoscopy screening and then do obtain a colonoscopy compared with those who do not get screened after the recommendation.…”
Section: Introductionmentioning
confidence: 99%
“…14 In another cohort trial, clinical prompts on the patient medical record significantly improved the probability that a screening test would be ordered. 15 Even when patients have had a prior colonoscopy, a physician reminder increases the use of surveillance colonoscopy. 16 Knowing that the recommendation of CRC screening is one of the strongest predictors of screening, it is important to discern the differences between those persons who receive a recommendation for CRC colonoscopy screening and then do obtain a colonoscopy compared with those who do not get screened after the recommendation.…”
Section: Introductionmentioning
confidence: 99%
“…Education alone does not seem to be an adequate method to improve screening rates. Seres et al [23] evaluated two comparison initiatives at the provider level to improve the quality of care in CRC screening: an evidence-based lecture regarding screening guidelines, compared to the lecture in addition to a written prompt on the patient chart for all applicable patients. The study found that clinical prompts significantly improved completion of CRC screenings among physician providers when compared to administering evidence-based lectures alone.…”
Section: Discussionmentioning
confidence: 99%
“…Such practice-related barriers to providing CRC screening may present greater hurdles for FPs than internists, particularly in rural and underserved areas. Tailored practice-based interventions [25] including reminder systems [26], clinical outreach, programs to monitor disparate care in practices, and the use of preventive medicine specialists, supported by information technology solutions and incentive programs, may increase screening within primary care offices. Mitigating such hurdles has the potential to increase recommendations of CRC screening in primary care practices.…”
Section: Discussionmentioning
confidence: 99%